Methylation of Tumor Suppressor Genes in Autoimmune Pancreatitis. Issue 5 (May 2017) - Kinugawa, Yasuhiro; Uehara, Takeshi; Sano, Kenji; Matsuda, Kazuyuki; Maruyama, Yasuhiro; Kobayashi, Yukihiro; Nakajima, Tomoyuki; Hamano, Hideaki; Kawa, Shigeyuki; Higuchi, Kayoko; Hosaka, Noriko; Shiozawa, Satoshi; et al.
Abstract : Objectives: Autoimmune pancreatitis (AIP) is a representative IgG4-related and inflammatory disease of unknown etiology. To clarify mechanisms of carcinogenesis resulting from AIP, we focused on methylation abnormalities and KRAS mutations in AIP. Methods: Six tumor suppressor genes ( NPTX2, Cyclin D2, FOXE1, TFPI2, ppENK, and p16 ) that exhibited hypermethylation in pancreatic carcinoma were selected for quantitative SYBR green methylation-specific polymerase chain reaction in 10 AIP specimens, 10 pancreatic adenocarcinoma cases without history of AIP containing carcinoma areas (CAs) and noncarcinoma areas (NCAs), and 11 normal pancreas (NP) samples. KRAS mutation in codons 12, 13, and 61 were also investigated using direct sequencing. Results: Hypermethylation events (≥10%) were identified in NPTX2, Cyclin D2, FOXE1, TFPI2, ppENK, and p16 in 1, 2, 2, 0, 2, and 0 CA cases, respectively, but not in these 6 candidate genes in AIP, NCA, and NP. However, the TFPI2 methylation ratio was significantly higher in AIP than NCA and NP. Direct sequencing results for KRAS showed no single-point mutations in AIP. Conclusions: These are the first studies characterizing methylation abnormalities in AIP. AIP's inflammatory condition may be related to carcinogenesis. Further study will elucidate methylation abnormalities associated with carcinogenesis in AIP.